Żywienie dzieci z dysfunkcjami neurologicznymi - Kasica-Bańkowska, Katarzyna (Logopedia Silesiana, 2012)
Nutrition of neurologically impaired childrenEnergy needs among neurologically impaired children are difficult to define, so malnutritionor overnutrition are common. Nutritional support should be integral part of therapy reducingmorbidity and improving rehabilitation effects. Considering multidisciplinary team working with neurologicallyimpaired children we should always remember about improving oromotor dysfunction andnutritional intervention.